Penggunaan Lembar Kegiatan Peserta Didik Materi Mikroalga sebagai Sumber Belajar Biologi: THE USE OF MICROALGAE MATERIAL STUDENT ACTIVITY SHEETS AS A SOURCE OF LEARNING BIOLOGY AND PRACTICUM ACTIVITY - Sufiyanto, Mohammad Imam; Khairunisa, Khairunisa (Fakultas Tarbiyah dan Ilmu Keguruan UIN Jurai Siwo, Lampung, 2023)
Student activity sheets are one of the Biology learning resource materials that are in great demand by students and the material delivered is microalgae is one of the components of the subject matter that can be used in the preparation of ecosystems contained in aquatic ecosystems that can be a source of student learning. Sourced from environmental aspects around Badur Beach, a sheet of activities for students in the microalgae practicum module was compiled. This research method uses descriptive qualitative by using data triangulation, namely observation, interviews, and documentation of the results of documentation written in the form of tables as one of the indicators in measuring the implementation of learning in the form of practicum in the classroom. The data collection instruments used are validity and response questionnaires. The sample in this study was 32 students in grade X of SMAN 3 Pamekasan and one biology teacher. The results showed that there is a lack of connection between understanding basic concepts and basic understanding of science in the context of everyday life. Teachers in learning biology SMA still do not use the environment as a learning resource in practicum learning in biology subjects at SMAN 3 Pamekasan. From these problems, one way to relate learning material to the context of everyday life is to do a practicum. Through simple practicum activities, students are directly expected to see real symptoms that are also related to the concept of the lesson, both natural conditions and conditions carried out through experiments.